2014
DOI: 10.3389/fpsyg.2014.00755
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with schizophrenia use prosody to encode contrastive discourse status?

Abstract: Patients with schizophrenia (SZ) often display social cognition disorders, including Theory of Mind (ToM) impairments and communication disruptions. Thought language disorders appear to be primarily a disruption of pragmatics, SZ can also experience difficulties at other linguistic levels including the prosodic one. Here, using an interactive paradigm, we showed that SZ individuals did not use prosodic phrasing to encode the contrastive status of discourse referents in French. We used a semi-spontaneous task t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 47 publications
1
19
2
7
Order By: Relevance
“…To do so, in the not-shared knowledge condition, target items appeared in black boxes and participants knew that they could have different shape/colour for objects in those boxes while in the shared knowledge condition, items appeared in white boxes and participants knew that it meant that their interlocutor shared the same objects as him/her. Second, in order to induce phonological prosodic variations, we manipulated the informational status of the second fragment since contrastive status of words is well known to lead to differences in AP phrasing [12,13,14]. To do so, we manipulated whether the noun or the adjective in the 2 nd fragment was the same or contrasted with the noun or the adjective in the 1 st fragment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To do so, in the not-shared knowledge condition, target items appeared in black boxes and participants knew that they could have different shape/colour for objects in those boxes while in the shared knowledge condition, items appeared in white boxes and participants knew that it meant that their interlocutor shared the same objects as him/her. Second, in order to induce phonological prosodic variations, we manipulated the informational status of the second fragment since contrastive status of words is well known to lead to differences in AP phrasing [12,13,14]. To do so, we manipulated whether the noun or the adjective in the 2 nd fragment was the same or contrasted with the noun or the adjective in the 1 st fragment.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-boundary lengthening and the presence of a typical fundamental frequency (f0) rise aligned with the last syllable of the AP are well known as the two main correlates of AP right boundaries [15,16,17,18]. For this reason, we considered that an AP right boundary was actually produced by the speaker after the target noun if (i) the f0 maximum hertz value of the last syllable of the target noun was at least 10% higher than that of the preceding low inflection point in the f0 curve and if (ii) the duration of the last syllable of the target noun was at least 10% longer than that the preceding syllable (see [14] for this procedure).…”
Section: Director's Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the clearest consensus across studies on focus and prosodic features in French is that prosodic phrasing, i.e., the grouping of words into melodic/rhythmic phonological units of different sizes, is one of the main strategies employed by French speakers to mark the difference between given and contrastive elements. Specifically, a number of studies have reported a tendency for a narrow-focused constituent to be parsed in a separate AP (Beyssade et al, 2009;Chen & Destruel, 2010;Dohen & Loevenbruck, 2004;Féry, 2001;Michelas et al, 2014). In operational terms, if two elements would typically be grouped into a single AP in a nonfocused context, then in case one of them is focused, a prosodic restructuring process isolates that element in a separate AP.…”
Section: Introductionmentioning
confidence: 99%
“…However, they produced the element that contrasted with a previously mispronounced element in a separate AP when they knew that the prompt conveyed false-belief about this element (e.g., [Les loups]AP [suivaient]AP [Mariloup]AP when "Mariloup" was mispronounced). As a consequence, when Mariloup was contrastive, an additional pitch accent was produced in the last syllable of "suivait" to isolate the noun from the preceding verb (see also Michelas et al, 2014). Rephrasing may also occur due to stress clash resolution, as described by Post (2011).…”
Section: General Discussion and Conclusionmentioning
confidence: 91%